DISTRIBUTED 2D TEMPERATURE SENSING DURING NANOPARTICLES ASSISTED LASER ABLATION BY MEANS OF HIGH-SCATTERING FIBER SENSORS - Ashikbayeva, Zhannat; Aitkulov, Arman; Jelbuldina, Madina; Issatayeva, Aizhan; Beisenova, Aidana; Molardi, Carlo; Saccomandi, Paola; Blanc, Wilfried; Inglezakis, Vassilis J.; Tosi, Daniele (Nature Research, 2020)
The high demand in effective and minimally invasive cancer treatments, namely thermal ablation, leads to the demand for real-time multi-dimensional thermometry to evaluate the treatment effectiveness, which can be also assisted by the use of nanoparticles. We report the results of 20-nm gold and magnetic iron oxide nanoparticles-assisted laser ablation on a porcine liver phantom. The experimental set-up consisting of high-scattering nanoparticle-doped fibers was operated by means of a scattering–level multiplexing arrangement and interrogated via optical backscattered reflectometry, together with a solid-state laser diode operating at 980 nm. The multiplexed 2-dimensional fiber arrangement based on nanoparticle-doped fibers allowed an accurate superficial thermal map detected in real-time.
Keywords: Research Subject Categories::TECHNOLOGY